Odpowiedzi

2009-12-29T09:32:51+01:00
X³+2x²-16x-32=0
x²(x+2)-16(x+2)=0
(x+2)(x-4)(x+4)=0
x1=-2, x2=4, x3=-4
2009-12-29T09:33:30+01:00
X³ + 2x² - 16x - 32 = 0
x²(x + 2) - 16(x + 2) = 0
(x + 2)(x² - 16) = 0
(x + 2)(x + 4)(x - 4) = 0
x + 2 = 0 lub x + 4 = 0 lub x - 4 = 0
x = -2 lub x = -4 lub x = 4
2009-12-29T10:43:33+01:00
X³ + 2x² - 16x - 32 = 0
metodą grupowania:

x²( x+2) - 16(x + 2) = 0
(x² - 16)(x+2) = 0

ze wzoru a² - b² = (a+b)(a-b)

(x +4)(x- 4) (x + 2) = 0

Iloczyn liczb jest = 0, gdy jedna z liczb jest =0
czyli:

x +4 = 0 lub x- 4= 0 lub x + 2 =0
x = - 4 lub x= 4 lub x = -2